DRUG DAMAGE OF THE LIVER IN TREATMENT OF REPRODUCTIVE FUNCTION IN WOMEN - Маслова Г. С. (World of Medicine and Biology, 2015)
In the article the modern data about leading pathogenetic mechanisms of drug liver lesions during treatment of liver reproductive function in women. The basic ways estrohen- metabolism of drugs and hestahenvmisnyh c omparative characteristics of potential hepatotoxic reactions of certain medicines. Using estrogens, progestogens and combinations thereof, including oral contraceptives, in patients at risk could rise to hepatic internally and externally hepatic cholestasis, and promote the progression of cholelithiasis, more rarely cause steatosis and steatohepatitis development, peliozu. It is noted that drug liver damage from pathogenic point of view can take advantage of the syndrome of cholestasis, cytolysis or mixed type. The algorithm hepatotoxic reactions and diagnostic approaches and approaches for pharmacological therapy, taking into account the type of damage to hepatocytes.